2021
DOI: 10.1002/pbc.29337
|View full text |Cite
|
Sign up to set email alerts
|

Body composition of patients with neuroblastoma using computed tomography

Abstract: Background: Computed tomography (CT) is often used to investigate muscle and fat mass in adult patients with cancer. However, this method has rarely been used in the pediatric cancer population. The present retrospective study aimed to investigate changes in body composition using CT during treatment in children with neuroblastoma.Procedure: CT images of 29 patients with high-risk neuroblastoma were retrospectively analyzed at diagnosis and longitudinally during treatment. The cross-sectional area of skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 15 publications
(36 reference statements)
0
10
1
Order By: Relevance
“…Similarly, previous studies using CT scans to examine changes in body composition have also not demonstrated a correlation between changes in BMI%ile and skeletal muscle 24,25 . Although these studies did not find a correlation between changes in anthropometric measurements such as BMI%ile or BSA and measures of adiposity (in contrast to the findings in our study), these differences may be attributable to heterogeneity in study populations or the methods used for adiposity assessment 18,24,25 . For example, the report by Joffe et al.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Similarly, previous studies using CT scans to examine changes in body composition have also not demonstrated a correlation between changes in BMI%ile and skeletal muscle 24,25 . Although these studies did not find a correlation between changes in anthropometric measurements such as BMI%ile or BSA and measures of adiposity (in contrast to the findings in our study), these differences may be attributable to heterogeneity in study populations or the methods used for adiposity assessment 18,24,25 . For example, the report by Joffe et al.…”
Section: Discussioncontrasting
confidence: 84%
“…Most studies reporting changes in body composition have examined BMI and predominantly focused on children with acute lymphoblastic leukemia (ALL), 13,14,28–30 with very few studies using imaging‐based body composition assessment across other childhood cancer diagnoses 18,24,25 . We expand on that literature by examining body composition in children, adolescents, and young adults with lymphoma and rhabdomyosarcoma and show that patients undergo a significant decline in SMD during the first few weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[82][83][84][85] It is an evaluation that involves high cost and radiation exposure and usually requires special programs and clinicians to quantify the amount of muscle and/or fat. However, patients undergoing abdominal CT for the evaluation of other clinical situations (eg, oncologic patients) 93 can undergo a retrospective image analysis of the L3 midpoint vertebral region to estimate the muscle area, which reflects body muscle mass in healthy populations and could be used in patients who are critically ill, despite difficulties in transporting this type of patient (sedated, mechanical ventilation, etc). 87 We found a few studies in pediatric patients that included specific populations, such as children with coronavirus disease 2019, neuroblastoma, etc.…”
Section: Ctmentioning
confidence: 99%